ACQUIRING ENGLISH VOCABULARY USING STORYTELLING - Muhammad Cajuizi, Alfzehra; Mandarani, Vidya (Language Horizon: Journal of Language Studies, 2025)
Vocabulary acquisition is a crucial component of English language learning; however, many students struggle to master it due to conventional teaching methods that fail to engage their emotional and cognitive faculties. Despite the application of various instructional strategies, there remains a notable lack of innovative and enjoyable approaches specifically for junior high school learners. This study investigates the effectiveness of the storytelling method in improving vocabulary mastery among 7th-grade students at SMP Muhammadiyah 5 Tulangan. Employing a quantitative methodology with a pre-experimental design, the research was conducted through three stages: a pre-test, an intervention using storytelling, and a post-test. The Wilcoxon Signed-Rank Test was used for analysis as the data did not follow a normal distribution. The findings revealed a statistically significant improvement in vocabulary scores post-intervention (p = 0.001), indicating the method’s efficacy. Storytelling fostered a more contextual and enjoyable learning environment and increased their motivation and participation. These results suggest that storytelling was a viable and interactive pedagogical alternative for improving vocabulary mastery in junior high school English education.